(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
During the last quarter of the eighteenth century and the first decades of the nineteenth, the flow of foreign artists, scholars and, aristocrats enlivened the Italian and especially the Roman scene, the fulcrum of artistic, antiquarian, and archaeological interests. Focusing on the field of the ‘Campagna’ such different approaches emerge and some recurring elements, as well as innovative visions and singular sensibilities. Dissemination of publications and prints was decisive in the elaboration of the individual and collective experience, including depiction of antiquities as they appeared to the eyes of observers, and of the fantastic images recalling perceptions and emotions. Keywords: Rome, Grand Tour, architecture, restoration, Roman Campagna.